Smart products: liability, timing of market introduction, and investments in product safety - Herbert Dawid; Gerd Muehlheusser (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper addresses the role of product liability for the emergence and development of smart products such as autonomous vehicles (AVs). We analyze how the liability regime affects innovative activities, as well as the timing of market introduction and market penetration of such smart products. We develop a dynamic model in which at each point in time, a potential (monopolistic) innovator decides on how much to invest in the safety stock of the smart product and on the product price, once it has been launched. Calibrating the model to the U.S. car market, our analysis reveals policy-relevant trade-offs when shifting more liability on the producers of AVs. First, while this improves the safety of AVs in the long run, the safety stock is accumulated more slowly. Second, it delays the market introduction of AVs, and also slows down market penetration, which hampers the innovator's incentives for safety investments in the short- and intermediate term. As a result, the safety level of AVs at a given point in time decreases as the liability regime becomes more stringent. Furthermore, there is a threshold for the innovator's burden of liability beyond which she forgoes to develop the AV altogether. Finally, we find that direct AV safety regulation is welfare-superior compared to a stringent liability regime, as it induces higher levels of AV safety in the short and intermediate term.
Keywords: O31; K13; L11; L62; 330; product innovation; liability; digital economy; autonomous vehicles; smart products; optimal investment dynamics